Analisa Penerimaan dan Strategi Pemasaran Apotek Herbal di Kota Bekasi - Andika Kristian; Wahono Sumaryono; Sri Widyastuti; Henky Lesmana (JRB-Jurnal Riset Bisnis, 2020)
Most pharmacies sold only large segments of herbal needs, there were not pharmacy that serves special herbal needs. This study aims to find out the possibility of special needs of herbal products can develop or not at Bekasi. The research was a descriptive explorative research by distributing questionnaires to 100 respondents in December 2017 to March 2018 then the result was processed by using SPSS software version 24 and basic statistic. The results of data processing were analyzed from aspects of the marketing mix. The results showed that nature’s pharmacy had not been accepted by the people at around of Bekasi but there was a business opportunity of new concept of nature’s pharmacy. Marketing strategy of nature pharmacies at around of Bekasi by applying nature’s pharmacy promotion system through counseling and promotion vigorously through advertisement in online media and providing vitamin products and herbal medicines completed with the right dosage form and the right type of herbal medicines.